Nanomolar Levels of Dimethylsulfoniopropionate, Dimethylsulfonioacetate, and Glycine Betaine Are Sufficient To Confer Osmoprotection to Escherichia coli - Cosquer, Anne (American Society for Microbiology, 1999)
We combined the use of low inoculation titers (300 ± 100 CFU/ml) and enumeration of culturable cells to measure the osmoprotective potentialities of dimethylsulfoniopropionate (DMSP), dimethylsulfonioacetate (DMSA), and glycine betaine (GB) for salt-stressed cultures of Escherichia coli. Dilute bacterial cultures were grown with osmoprotectant concentrations that encompassed the nanomolar levels of GB and DMSP found in nature and the millimolar levels of osmoprotectants used in standard laboratory osmoprotection bioassays. Nanomolar concentrations of DMSA, DMSP, and GB were sufficient to enhance the salinity tolerance of E. coli cells expressing only the ProU high-affinity general osmoporter. In contrast, nanomolar levels of osmoprotectants were ineffective with a mutant strain (GM50) that expressed only the low-affinity ProP osmoporter. Transport studies showed that DMSA and DMSP, like GB, were taken up via both ProU and ProP. Moreover, ProU displayed higher affinities for the three osmoprotectants than ProP displayed, and ProP, like ProU, displayed much higher affinities for GB and DMSA than for DMSP. Interestingly, ProP did not operate at substrate concentrations of 200 nM or less, whereas ProU operated at concentrations ranging from 1 nM to millimolar levels. Consequently, proU(+) strains of E. coli, but not the proP(+) strain GM50, could also scavenge nanomolar levels of GB, DMSA, and DMSP from oligotrophic seawater. The physiological and ecological implications of these observations are discussed.